Mathematical Modeling of a Non-Isothermal Flow in a Porous Medium Considering Gas Hydrate Decomposition: A Review - Stanislav L. Borodin; Nail G. Musakaev; Denis S. Belskikh (Mathematics, 2022)
Deposits of natural gas hydrates are some of the most promising sources of hydrocarbons. According to studies, at the current level of natural gas consumption, the traditional reserves will last for about 50 years, and the gas hydrate deposits will last for at least 250 years. Therefore, interest in the study of gas hydrates is associated first of all with gas production from gas hydrate deposits. Additionally, gas hydrates are widely studied for solving practical problems, such as transportation and storage of natural gas, utilization of industrial gases and environmental and technological disasters associated with gas hydrates. When solving practical problems related to gas hydrates, in addition to laboratory and field studies, mathematical modeling is also widely used. This article presents the mathematical models of non-isothermal flow in a porous medium considering the decomposition of gas hydrate. The general forms of the mass conservation equations, Darcy’s law and the energy conservation equation are given. The article also presents derivations of the equations for taking into account the latent heat of phase transitions and non-isothermal filtration parameters for the energy conservation equation. This may be useful for researchers to better understand the construction of the model. For the parameters included in the basic equations, various dependencies are used in different works. In all the articles found, most often there was an emphasis on one or two of the parameters. The main feature of this article is summarizing various dependencies for a large number of parameters. Additionally, graphs of these dependencies are presented so that the reader can independently evaluate the differences between them. The most preferred dependencies for calculations are noted and explained.